Iodine-resistant packaging material and preparation method thereof
By adopting a multi-layer structure iodine-resistant packaging material, using composite fillers and tea polyphenols in the modified PVA coating, the problems of iodine loss of existing medicinal packaging materials when protecting drugs and the easy destruction of aluminum foil layers are solved, and high isolation performance and mechanical properties are improved to ensure the safety of drug preservation and identification.
Patent Information
- Application Number
- CN202411783824.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing pharmaceutical packaging materials have problems such as iodine loss and easy destruction of aluminum foil layer when protecting drugs, and lack anti-counterfeiting labels and effective heat sealing strength and barrier properties, which affect the preservation and identification of drugs.
The multi-layer structural packaging material consisting of aluminum foil layer, vinyl resin heat seal coating, modified PVA coating, VC glue coating, polyurethane heat seal coating and polyvinyl chloride sheet are used to improve the iodine resistance, oxygen resistance and mechanical properties of the packaging material by modifying the composite filler of concave and convex rod soil, wood fiber and silica in the PVA coating.
It realizes the high insulation performance, strong corrosion resistance and chemical stability of packaging materials, effectively protects drugs from the influence of the external environment, and improves the safety of drug storage and identification.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of iodine barrier material preparation, and in particular relates to an iodine barrier packaging material and a preparation method thereof. Background Art
[0002] Packaging materials are widely used in actual production and life, such as food, medicine and other fields. Blister packaging is the fastest-growing flexible packaging material in recent years, and it is also the main packaging form in other fields such as medicine, health products, and food. Blister packaging is also called a linkage process in which industrial pure aluminum foil is used as the base material, and the text pattern is printed on the surface of the aluminum foil by gravure printing technology and roller coating method on the pharmaceutical PTP (Press Through Packing) aluminum foil coating machine, and a protective layer is applied, and an adhesive layer is applied on the other side of the aluminum foil. However, for the existing market packaged medicines, for medicines containing a certain amount of iodine, ordinary PTP aluminum foil is used for packaging. Not only does the loss of iodine greatly exceed the requirement, but the aluminum foil layer is easily destroyed by iodine, and the protective effect of the packaging cannot be achieved at all. Since the aluminum foil for pharmaceutical packaging has no anti-counterfeiting mark, it is easy to be counterfeited, which is not conducive to the preservation and identification of medicines. In addition, in the control of the pharmaceutical PTP aluminum foil coating process, there are problems such as low heat sealing strength and barrier performance of blister packaging, which cannot guarantee the safety and effectiveness of the medicine. Therefore, it is imperative to carry out research on pharmaceutical packaging materials with high isolation performance, strong corrosion resistance and chemical stability, especially packaging materials that can effectively protect drugs from the influence of the external environment.
[0003] In the prior art, for example, patent document CN220841724U provides an iodine-barrier aluminum foil blister packaging structure, which discloses the corresponding iodine-barrier structure, but does not disclose how the iodine-barrier structure is prepared. This patent is also an earlier patent technology of the applicant; patent document CN117183483A provides an iodine-barrier packaging material, including a cover film and a base film, the cover film includes a paper layer, a first aluminum foil layer and a first PET layer stacked in sequence from top to bottom, and the base film includes a glue layer, a second PET layer, a second aluminum foil layer, and a polyamide layer arranged in sequence from top to bottom. In the preparation process of the polyamide layer, materials such as graphite carbon nitride are used, and the cost is relatively high. In addition, the performance of the obtained packaging material, except for iodine barrier, needs to be further improved in other aspects. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an iodine barrier packaging material and a preparation method thereof, which has good barrier properties such as iodine barrier and oxygen barrier, good mechanical properties and excellent comprehensive indicators.
[0005] In order to achieve the above object, the present invention adopts the following technical solution: In a first aspect, the present invention provides an iodine-blocking packaging material, which is composed of an aluminum foil layer, a vinyl resin heat-sealing coating, a modified PVA coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; Wherein, the modified PVA coating is obtained by coating with a PVA coating solution, and the preparation of the PVA coating solution comprises the following steps: Add PVA resin to deionized water, stir at 80-90°C for 0.5-4h, then cool to 25-35°C, then add modified composite filler and stir for 0.5-3h; after treatment, cool to room temperature to obtain the product.
[0006] In the above technical solution, the structure of the packaging material can be further understood by referring to the prior art, such as patent document CN220841724U, and the technical solution provided by the present invention is a further study based on the prior art. It should be particularly emphasized that, as a practical requirement, the aluminum foil layer is also printed with gravure aluminum foil ink and is subjected to corresponding coating protection.
[0007] Preferably, the mass ratio of PVA resin, deionized water and modified composite filler is 100:20-35:8-15.
[0008] Preferably, the preparation of the modified composite filler comprises the following steps: S1. Modification of attapulgite: firstly, attapulgite is mixed with sodium hydroxide and then subjected to high temperature treatment. After the treatment, it is added into a hydrochloric acid solution and subjected to shaking treatment. After the treatment, it is subjected to centrifugation, washing, drying treatment, and finally sieving to obtain modified attapulgite; S2. Modification of wood fiber: adding wood fiber and sodium chloroacetate to water for heating reaction, adding sodium hydroxide after the reaction is completed, and reacting at room temperature, washing to neutrality after the reaction is completed, and drying to obtain modified wood fiber; S3, modification of silicon dioxide: adding silicon dioxide to the mixed solution, and then treating it under heating and stirring conditions. After the treatment is completed, centrifuging, washing and drying are performed to obtain modified silicon dioxide; S4. Compounding of tea polyphenols: adding the modified attapulgite obtained in step S1, the modified wood fiber obtained in step S2 and the modified silicon dioxide obtained in step S3 into water, stirring and then adding tea polyphenols, stirring under heating conditions, centrifuging and drying after the treatment, to obtain a modified composite filler.
[0009] Preferably, in step S1, the mass ratio of attapulgite to sodium hydroxide is 1:0.4-0.8, the high temperature treatment temperature is 790-805°C, and the treatment time is 0.5-4h.
[0010] Preferably, in step S1, the concentration of the hydrochloric acid solution is 0.5-2.5 mol / L; the mass ratio of attapulgite to the hydrochloric acid solution is 1 g:8-12 mL; the shaking treatment rate is 150-200 rpm, and the shaking treatment time is 0.5-2 h; and the sieving mesh number is 100-200 mesh.
[0011] Preferably, in step S2, the mass ratio of wood fiber, sodium chloroacetate, water and sodium hydroxide is 1:1.2~2:20~30:1~1.5; the heating reaction temperature is 55~70°C, the heating reaction time is 2~8h; and the reaction time at room temperature is 12~36h.
[0012] Preferably, in step S3, the mixed solution is obtained by mixing concentrated sulfuric acid and hydrogen peroxide, the concentration of concentrated sulfuric acid is 11-18 mol / L, the concentration of hydrogen peroxide is 8-12 mol / L, and the volume ratio of concentrated sulfuric acid to hydrogen peroxide is 1:2-4; the amount ratio of silicon dioxide to the mixed solution is 1 g:5-8 mL; the heating and stirring treatment temperature is 35-50 ° C, the treatment time is 0.5-4 h, and the stirring rate of the heating and stirring is 80-150 rpm.
[0013] Preferably, in step S4, the mass ratio of modified attapulgite, modified wood fiber, modified silica, tea polyphenols and water is 1:2~3:0.5~1:0.1~0.3:8~12; the heating temperature is 30~35°C, the stirring treatment time is 1~4h, and the stirring rate is 60~120rpm.
[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned iodine-blocking packaging material, comprising the following steps: (1) coating a vinyl resin heat-sealing adhesive on the surface of the aluminum foil layer and drying the adhesive to form a vinyl resin heat-sealing coating; (2) applying a PVA coating liquid on the surface of the vinyl resin heat seal coating, and drying to form a modified PVA coating; (3) Applying VC glue on the surface of the modified PVA coating and drying to form a VC glue coating; (4) applying polyurethane heat-sealing adhesive on the surface of the VC glue coating, and drying to form a polyurethane heat-sealing coating to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
[0015] Preferably, the coating amount of the vinyl resin heat sealant is 5 to 8 g / m 2 ; The coating amount of PVA coating liquid is 4~6 g / m 2 ; The coating amount of VC glue is 4~6 g / m 2 ; The coating amount of polyurethane heat sealant is 5~8 g / m 2 .
[0016] Compared with the prior art, the present invention has the following beneficial effects: The iodine-barrier packaging material provided by the present invention is composed of a multi-layer structure, has good adhesion, good mechanical strength, has the functions of blocking iodine and blocking water and oxygen, and has good comprehensive performance.
[0017] In the iodine-blocking packaging material provided by the present invention, the modified PVA coating plays a key iodine-blocking function, and is prepared by modifying common attapulgite, wood fiber and silica. Specifically, attapulgite is an inorganic filler, and wood fiber is an organic filler. The combination of organic and inorganic fillers ensures the compactness of the filling and the use effect, but the use of the two will reduce the mechanical properties of the packaging material to a certain extent. Therefore, a small amount of silica is also used in the present invention, and the composite use of the three ensures the mechanical properties and comprehensive performance of the packaging material; the film-forming density of the PVA resin will greatly affect the iodine-blocking effect, so the present invention carries out targeted modification of the above three substances, wherein the attapulgite is first subjected to a high-temperature alkali melting treatment, which is beneficial to enriching its pores and improving the subsequent adsorption of tea polyphenols. The invention discloses a method for preparing the composite material of the present invention. The present ... In summary, the present invention selects attapulgite, silica and wood fiber, all of which are rich in hydroxyl groups and the like, and can efficiently composite-graft with each other in the form of hydrogen bonds and the like, and can also react with tea polyphenols, so that the tea polyphenols can be combined with the filler system in the form of hydrogen bonds, adsorption and the like, thereby ensuring the dispersibility and stability of the filler system; the raw materials of each substance are relatively common and the cost is controllable.
[0018] The preparation method of the iodine-blocking packaging material provided by the present invention mainly uses a four-layer coating process, is simple, and is easy to implement. DETAILED DESCRIPTION
[0019] Embodiments of the present invention are described in detail below. All embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0020] In the present invention, the particle size of silicon dioxide is about 20 nm.
[0021] In the present invention, VC glue was purchased from Xi'an Tianyi Adhesive Materials Co., Ltd.; vinyl resin heat sealant was purchased from Shanghai Weikai Optoelectronic New Materials Co., Ltd. with a brand name of VC-1100; PVA resin was purchased from Jining Fangyu Chemical Co., Ltd. with a brand name of 1799; and polyurethane heat sealant was purchased from Michelman (Shanghai) Chemical Trading Co., Ltd.
[0022] In the present invention, the remaining matters not described are all conventional means known to those skilled in the art (such as coating method, drying and compounding, etc.); materials without source description are all commercially available.
[0023] It should be noted that the structure of each layer in the present invention can be adjusted according to actual needs, such as the thickness can be selected as follows: the thickness of the aluminum foil layer is 0.032 mm, the thickness of the polyvinyl chloride sheet is 0.03 mm; the thickness of the vinyl resin heat-sealing coating, modified PVA coating, VC glue coating, and polyurethane heat-sealing coating are all 0.015 mm.
[0024] In the present invention, the concentration of hydrogen peroxide is 9 mol / L, and the concentration of concentrated sulfuric acid is 18 mol / L.
[0025] The coating speed and drying temperature of vinyl resin heat sealant, PVA coating liquid, VC glue and polyurethane heat sealant can be selected according to the actual characteristics of the product. For example, the coating speed of VC glue can be 50m / min, the drying temperature is about 160~175℃, and the composite pressure of semi-finished product and polyvinyl chloride sheet is 2.5kg / cm 2 The selection of the above process parameters can be actually selected by those skilled in the art as needed. The above parameters of the present invention are only examples and do not constitute a limitation on the protection scope of the present invention. The specific implementation is subject to what can be achieved by those skilled in the art.
[0026] Example 1
[0027] An iodine-blocking packaging material, which consists of an aluminum foil layer, a vinyl resin heat-sealing coating, a modified PVA coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; Wherein, the modified PVA coating is obtained by coating with a PVA coating solution, and the preparation of the PVA coating solution comprises the following steps: According to the mass ratio of PVA resin, deionized water and modified composite filler being 100:30:9.5, PVA resin is added to deionized water and stirred at 85°C for 2.5h. Then the temperature is lowered to 30°C and the modified composite filler is added and stirred for 2h. After the treatment, the temperature is lowered to room temperature to obtain the product.
[0028] The preparation of the modified composite filler comprises the following steps: S1. Modification of attapulgite: firstly, attapulgite and sodium hydroxide were mixed in a mass ratio of 1:0.5 and then subjected to high temperature treatment (795°C, 1.5h). After the treatment, the mixture was added into a 1.6mol / L hydrochloric acid solution and subjected to shaking treatment (180rpm, 1.5h). After the treatment, the mixture was centrifuged, washed, dried, and finally sieved through 150 mesh to obtain modified attapulgite. The mass ratio of attapulgite to hydrochloric acid solution was 1g:10mL. S2. Modification of wood fiber: according to the mass ratio of wood fiber, sodium chloroacetate, water and sodium hydroxide of 1:1.5:23:1.2, wood fiber and sodium chloroacetate are added to water for heating reaction (65°C, 4h), and sodium hydroxide is added after the reaction is completed, and the reaction is continued at room temperature for 18h. After the reaction is completed, the modified wood fiber is obtained by washing to neutrality and drying. S3. Modification of silicon dioxide: silicon dioxide is added to a mixed solution (concentrated sulfuric acid and hydrogen peroxide are mixed in a volume ratio of 1:3), and then treated under heating and stirring conditions (40°C, 2h, 100rpm). After the treatment, the modified silicon dioxide is obtained by centrifugation, washing and drying. The amount ratio of silicon dioxide to the mixed solution is 1g:6mL. S4. Compounding of tea polyphenols: according to the mass ratio of modified attapulgite, modified wood fiber, modified silica, tea polyphenols and water being 1:2.5:0.7:0.2:10, the modified attapulgite obtained in step S1, the modified wood fiber obtained in step S2 and the modified silica obtained in step S3 are added into water, and tea polyphenols are added after stirring. The mixture is stirred under heating conditions (35°C, 2h, 80rpm). After the treatment, it is centrifuged and dried to obtain a modified composite filler.
[0029] In this embodiment, a method for preparing the above-mentioned iodine-blocking packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 6 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of the vinyl resin heat seal coating, the 2 Apply the PVA coating liquid with a coating amount of , and form a modified PVA coating after drying; (3) On the surface of the modified PVA coating, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, according to 5.2 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
[0030] Example 2
[0031] An iodine-blocking packaging material, which consists of an aluminum foil layer, a vinyl resin heat-sealing coating, a modified PVA coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; Wherein, the modified PVA coating is obtained by coating with a PVA coating solution, and the preparation of the PVA coating solution comprises the following steps: According to the mass ratio of PVA resin, deionized water and modified composite filler being 100:28:10, PVA resin is added to deionized water, stirred at 86°C for 2h, then cooled to 30°C and then the modified composite filler is added and stirred for 2.5h; after the treatment, the temperature is cooled to room temperature to obtain the product.
[0032] The preparation of the modified composite filler comprises the following steps: S1. Modification of attapulgite: firstly, attapulgite and sodium hydroxide were mixed in a mass ratio of 1:0.45 and then subjected to high temperature treatment (800°C, 1h). After the treatment, the mixture was added into a 1.5mol / L hydrochloric acid solution and subjected to shaking treatment (180rpm, 1.5h). After the treatment, the mixture was centrifuged, washed, dried, and finally sieved through 150 mesh to obtain modified attapulgite. The mass ratio of attapulgite to hydrochloric acid solution was 1g:9mL. S2. Modification of wood fiber: according to the mass ratio of wood fiber, sodium chloroacetate, water and sodium hydroxide of 1:1.5:23:1.2, wood fiber and sodium chloroacetate are added to water for heating reaction (60°C, 4.5h), and sodium hydroxide is added after the reaction is completed, and the reaction is continued at room temperature for 18h. After the reaction is completed, the modified wood fiber is obtained by washing to neutrality and drying. S3. Modification of silicon dioxide: silicon dioxide is added to a mixed solution (concentrated sulfuric acid and hydrogen peroxide are mixed in a volume ratio of 1:3), and then treated under heating and stirring conditions (40°C, 2.5h, 120rpm). After the treatment, the modified silicon dioxide is obtained by centrifugation, washing and drying. The amount ratio of silicon dioxide to the mixed solution is 1g:6mL. S4. Compounding of tea polyphenols: according to the mass ratio of modified attapulgite, modified wood fiber, modified silica, tea polyphenols and water being 1:2.6:0.6:0.22:10, the modified attapulgite obtained in step S1, the modified wood fiber obtained in step S2 and the modified silica obtained in step S3 are added into water, and tea polyphenols are added after stirring. The mixture is stirred under heating conditions (35°C, 2h, 80rpm). After the treatment, it is centrifuged and dried to obtain a modified composite filler.
[0033] In this embodiment, a method for preparing the above-mentioned iodine-blocking packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 6 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of the vinyl resin heat seal coating, the 2 Apply the PVA coating liquid with a coating amount of , and form a modified PVA coating after drying; (3) On the surface of the modified PVA coating, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, according to 5.2 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
[0034] Example 3
[0035] An iodine-blocking packaging material, which consists of an aluminum foil layer, a vinyl resin heat-sealing coating, a modified PVA coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; Wherein, the modified PVA coating is obtained by coating with a PVA coating solution, and the preparation of the PVA coating solution comprises the following steps: According to the mass ratio of PVA resin, deionized water and modified composite filler being 100:33:10.5, PVA resin is added to deionized water and stirred at 85°C for 2.5h. Then the temperature is lowered to 30°C and the modified composite filler is added and stirred for 2h. After the treatment, the temperature is lowered to room temperature to obtain the product.
[0036] Wherein, the preparation of the modified composite filler comprises the following steps: S1. Modification of attapulgite: firstly, attapulgite and sodium hydroxide were mixed in a mass ratio of 1:0.5 and then subjected to high temperature treatment (805°C, 1h). After the treatment, the mixture was added into a 1.7mol / L hydrochloric acid solution and subjected to shaking treatment (180rpm, 1.5h). After the treatment, the mixture was centrifuged, washed, dried, and finally sieved through 150 mesh to obtain modified attapulgite. The mass ratio of attapulgite to hydrochloric acid solution was 1g:11mL. S2. Modification of wood fiber: according to the mass ratio of wood fiber, sodium chloroacetate, water and sodium hydroxide of 1:1.6:22:1.3, wood fiber and sodium chloroacetate are added to water for heating reaction (65°C, 4h), and sodium hydroxide is added after the reaction is completed, and the reaction is continued at room temperature for 24h. After the reaction is completed, the modified wood fiber is obtained by washing to neutrality and drying. S3. Modification of silicon dioxide: silicon dioxide is added to a mixed solution (concentrated sulfuric acid and hydrogen peroxide are mixed in a volume ratio of 1:3), and then treated under heating and stirring conditions (45°C, 1.5h, 100rpm). After the treatment, the modified silicon dioxide is obtained by centrifugation, washing and drying. The amount ratio of silicon dioxide to the mixed solution is 1g:5.5mL. S4. Compounding of tea polyphenols: according to the mass ratio of modified attapulgite, modified wood fiber, modified silica, tea polyphenols and water being 1:2.6:0.72:0.2:11, the modified attapulgite obtained in step S1, the modified wood fiber obtained in step S2 and the modified silica obtained in step S3 are added into water, and tea polyphenols are added after stirring. The mixture is stirred under heating conditions (35°C, 2h, 80rpm). After the treatment, it is centrifuged and dried to obtain a modified composite filler.
[0037] In this embodiment, a method for preparing the above-mentioned iodine-blocking packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 6 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of the vinyl resin heat seal coating, the 2 Apply the PVA coating liquid with a coating amount of , and form a modified PVA coating after drying; (3) On the surface of the modified PVA coating, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, according to 5.2 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
[0038] Comparative Example 1
[0039] Compared with Example 1, the attapulgite in Comparative Example 1 is not modified, that is, step S1 is omitted. Specifically, an iodine-blocking packaging material is composed of an aluminum foil layer, a vinyl resin heat-sealing coating, a modified PVA coating, a VC glue coating, a polyurethane heat-sealing coating, and a polyvinyl chloride sheet from top to bottom; Wherein, the modified PVA coating is obtained by coating with a PVA coating solution, and the preparation of the PVA coating solution comprises the following steps: According to the mass ratio of PVA resin, deionized water and modified composite filler being 100:30:9.5, PVA resin is added to deionized water and stirred at 85°C for 2.5h. Then the temperature is lowered to 30°C and the modified composite filler is added and stirred for 2h. After the treatment, the temperature is lowered to room temperature to obtain the product.
[0040] Wherein, the preparation of the modified composite filler comprises the following steps: S1. Take attapulgite and set aside; S2. Modification of wood fiber: according to the mass ratio of wood fiber, sodium chloroacetate, water and sodium hydroxide of 1:1.5:23:1.2, wood fiber and sodium chloroacetate are added to water for heating reaction (65°C, 4h), and sodium hydroxide is added after the reaction is completed, and the reaction is continued at room temperature for 18h. After the reaction is completed, the modified wood fiber is obtained by washing to neutrality and drying. S3. Modification of silicon dioxide: silicon dioxide is added to a mixed solution (concentrated sulfuric acid and hydrogen peroxide are mixed in a volume ratio of 1:3), and then treated under heating and stirring conditions (40°C, 2h, 100rpm). After the treatment, the modified silicon dioxide is obtained by centrifugation, washing and drying. The amount ratio of silicon dioxide to the mixed solution is 1g:6mL. S4. Compounding of tea polyphenols: according to the mass ratio of attapulgite, modified wood fiber, modified silica, tea polyphenols and water being 1:2.5:0.7:0.2:10, the attapulgite in step S1, the modified wood fiber obtained in step S2 and the modified silica obtained in step S3 are added into water, stirred and then tea polyphenols are added, stirred under heating conditions (35°C, 2h, 80rpm), and after the treatment, centrifuged and dried to obtain the modified composite filler.
[0041] In this comparative example, a method for preparing the above-mentioned iodine-blocking packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 6 g / m 2Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of the vinyl resin heat seal coating, the 2 Apply the PVA coating liquid with a coating amount of , and form a modified PVA coating after drying; (3) On the surface of the modified PVA coating, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, according to 5.2 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
[0042] Comparative Example 2
[0043] Compared with Example 1, the wood fiber is not modified in Comparative Example 2, that is, step S2 is omitted. Specifically, an iodine-blocking packaging material is composed of an aluminum foil layer, a vinyl resin heat-sealing coating, a modified PVA coating, a VC glue coating, a polyurethane heat-sealing coating, and a polyvinyl chloride sheet from top to bottom; Wherein, the modified PVA coating is obtained by coating with a PVA coating solution, and the preparation of the PVA coating solution comprises the following steps: According to the mass ratio of PVA resin, deionized water and modified composite filler being 100:30:9.5, PVA resin is added to deionized water and stirred at 85°C for 2.5h. Then the temperature is lowered to 30°C and the modified composite filler is added and stirred for 2h. After the treatment, the temperature is lowered to room temperature to obtain the product.
[0044] Wherein, the preparation of the modified composite filler comprises the following steps: S1. Modification of attapulgite: firstly, attapulgite and sodium hydroxide were mixed in a mass ratio of 1:0.5 and then subjected to high temperature treatment (795°C, 1.5h). After the treatment, the mixture was added into a 1.6mol / L hydrochloric acid solution and subjected to shaking treatment (180rpm, 1.5h). After the treatment, the mixture was centrifuged, washed, dried, and finally sieved through 150 mesh to obtain modified attapulgite. The mass ratio of attapulgite to hydrochloric acid solution was 1g:10mL. S2, take wood fiber and set aside; S3. Modification of silicon dioxide: silicon dioxide is added to a mixed solution (concentrated sulfuric acid and hydrogen peroxide are mixed in a volume ratio of 1:3), and then treated under heating and stirring conditions (40°C, 2h, 100rpm). After the treatment, the modified silicon dioxide is obtained by centrifugation, washing and drying. The amount ratio of silicon dioxide to the mixed solution is 1g:6mL. S4. Compounding of tea polyphenols: according to the mass ratio of modified attapulgite, wood fiber, modified silica, tea polyphenols and water being 1:2.5:0.7:0.2:10, the modified attapulgite obtained in step S1, the wood fiber in step S2 and the modified silica obtained in step S3 are added into water, and tea polyphenols are added after stirring. The mixture is stirred under heating conditions (35°C, 2h, 80rpm). After the treatment, it is centrifuged and dried to obtain a modified composite filler.
[0045] In this comparative example, a method for preparing the above-mentioned iodine-blocking packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 6 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of the vinyl resin heat seal coating, the 2 Apply the PVA coating liquid with a coating amount of , and form a modified PVA coating after drying; (3) On the surface of the modified PVA coating, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, according to 5.2 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
[0046] Comparative Example 3
[0047] Compared with Example 1, the silicon dioxide in Comparative Example 3 is not modified, that is, step S3 is omitted. Specifically, an iodine-blocking packaging material is composed of an aluminum foil layer, a vinyl resin heat-sealing coating, a modified PVA coating, a VC glue coating, a polyurethane heat-sealing coating, and a polyvinyl chloride sheet from top to bottom; Wherein, the modified PVA coating is obtained by coating with a PVA coating solution, and the preparation of the PVA coating solution comprises the following steps: According to the mass ratio of PVA resin, deionized water and modified composite filler being 100:30:9.5, PVA resin is added to deionized water and stirred at 85°C for 2.5h. Then the temperature is lowered to 30°C and the modified composite filler is added and stirred for 2h. After the treatment, the temperature is lowered to room temperature to obtain the product.
[0048] Wherein, the preparation of the modified composite filler comprises the following steps: S1. Modification of attapulgite: firstly, attapulgite and sodium hydroxide were mixed in a mass ratio of 1:0.5 and then subjected to high temperature treatment (795°C, 1.5h). After the treatment, the mixture was added into a 1.6mol / L hydrochloric acid solution and subjected to shaking treatment (180rpm, 1.5h). After the treatment, the mixture was centrifuged, washed, dried, and finally sieved through 150 mesh to obtain modified attapulgite. The mass ratio of attapulgite to hydrochloric acid solution was 1g:10mL. S2. Modification of wood fiber: according to the mass ratio of wood fiber, sodium chloroacetate, water and sodium hydroxide of 1:1.5:23:1.2, wood fiber and sodium chloroacetate are added to water for heating reaction (65°C, 4h), and sodium hydroxide is added after the reaction is completed, and the reaction is continued at room temperature for 18h. After the reaction is completed, the modified wood fiber is obtained by washing to neutrality and drying. S3, take silicon dioxide and set aside; S4. Compounding of tea polyphenols: according to the mass ratio of modified attapulgite, modified wood fiber, silicon dioxide, tea polyphenols and water being 1:2.5:0.7:0.2:10, the modified attapulgite obtained in step S1, the modified wood fiber obtained in step S2 and the silicon dioxide in step S3 are added into water, and tea polyphenols are added after stirring. The mixture is stirred under heating conditions (35°C, 2h, 80rpm). After the treatment, it is centrifuged and dried to obtain a modified composite filler.
[0049] In this comparative example, a method for preparing the above-mentioned iodine-blocking packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 6 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of the vinyl resin heat seal coating, the 2 Apply the PVA coating liquid with a coating amount of , and form a modified PVA coating after drying; (3) On the surface of the modified PVA coating, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, according to 5.2 g / m 2Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
[0050] Comparative Example 4
[0051] Compared with Example 1, tea polyphenols are not added in Comparative Example 4. Specifically, an iodine-blocking packaging material is composed of an aluminum foil layer, a vinyl resin heat-sealing coating, a modified PVA coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; Wherein, the modified PVA coating is obtained by coating with a PVA coating solution, and the preparation of the PVA coating solution comprises the following steps: According to the mass ratio of PVA resin, deionized water and modified composite filler being 100:30:9.5, PVA resin is added to deionized water and stirred at 85°C for 2.5h. Then the temperature is lowered to 30°C and the modified composite filler is added and stirred for 2h. After the treatment, the temperature is lowered to room temperature to obtain the product.
[0052] Wherein, the preparation of the modified composite filler comprises the following steps: S1. Modification of attapulgite: firstly, attapulgite and sodium hydroxide were mixed in a mass ratio of 1:0.5 and then subjected to high temperature treatment (795°C, 1.5h). After the treatment, the mixture was added into a 1.6mol / L hydrochloric acid solution and subjected to shaking treatment (180rpm, 1.5h). After the treatment, the mixture was centrifuged, washed, dried, and finally sieved through 150 mesh to obtain modified attapulgite. The mass ratio of attapulgite to hydrochloric acid solution was 1g:10mL. S2. Modification of wood fiber: according to the mass ratio of wood fiber, sodium chloroacetate, water and sodium hydroxide of 1:1.5:23:1.2, wood fiber and sodium chloroacetate are added to water for heating reaction (65°C, 4h), and sodium hydroxide is added after the reaction is completed, and the reaction is continued at room temperature for 18h. After the reaction is completed, the modified wood fiber is obtained by washing to neutrality and drying. S3. Modification of silicon dioxide: silicon dioxide is added to a mixed solution (concentrated sulfuric acid and hydrogen peroxide are mixed in a volume ratio of 1:3), and then treated under heating and stirring conditions (40°C, 2h, 100rpm). After the treatment, the modified silicon dioxide is obtained by centrifugation, washing and drying. The amount ratio of silicon dioxide to the mixed solution is 1g:6mL. S4. Composite: according to the mass ratio of modified attapulgite, modified wood fiber, modified silicon dioxide and water being 1:2.5:0.7:10, the modified attapulgite obtained in step S1, the modified wood fiber obtained in step S2 and the modified silicon dioxide obtained in step S3 are added into water, and stirred under heating conditions (35°C, 2h, 80rpm). After the treatment, the mixture is centrifuged and dried to obtain a modified composite filler.
[0053] In this comparative example, a method for preparing the above-mentioned iodine-blocking packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 6 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of the vinyl resin heat seal coating, the 2 Apply the PVA coating liquid with a coating amount of , and form a modified PVA coating after drying; (3) On the surface of the modified PVA coating, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, according to 5.2 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
[0054] The iodine-blocking packaging materials prepared in Example 1 and Comparative Examples 1 to 4 were tested in the following manner: Iodine barrier performance test: The above-mentioned iodine barrier packaging material is made into an iodine cap, and an iodine-containing molecular drug is placed in it. After standing for 2 months, the iodine content is analyzed using potentiometric analysis.
[0055] Oxygen permeability test: The test is carried out in accordance with GB / T1038.1-2022.
[0056] Tensile strength test: refer to GB / T 1040.3-2006.
[0057] The specific test results are shown in Table 1.
[0058] Table 1 Performance test results
[0059] It can be seen from Table 1 that the iodine-barrier packaging material prepared in the present invention has good iodine-barrier and oxygen-barrier properties, good tensile strength and excellent comprehensive performance.
[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An iodine-blocking packaging material, characterized in that: From top to bottom, it is composed of an aluminum foil layer, a vinyl resin heat-seal coating, a modified PVA coating, a VC glue coating, a polyurethane heat-seal coating, and a polyvinyl chloride sheet; Wherein, the modified PVA coating is obtained by coating with a PVA coating solution, and the preparation of the PVA coating solution comprises the following steps: Add PVA resin to deionized water, stir at 80-90°C for 0.5-4h, then cool to 25-35°C, then add modified composite filler and stir for 0.5-3h; after treatment, cool to room temperature to obtain the product.
2. The iodine-blocking packaging material according to claim 1, characterized in that: The mass ratio of PVA resin, deionized water and modified composite filler is 100:20~35:8~15.
3. The iodine-blocking packaging material according to claim 1, characterized in that: The preparation of the modified composite filler comprises the following steps: S1. Modification of attapulgite: firstly, attapulgite is mixed with sodium hydroxide and then subjected to high temperature treatment. After the treatment, it is added into a hydrochloric acid solution and subjected to shaking treatment. After the treatment, it is subjected to centrifugation, washing, drying treatment, and finally sieving to obtain modified attapulgite; S2. Modification of wood fiber: adding wood fiber and sodium chloroacetate to water for heating reaction, adding sodium hydroxide after the reaction is completed, and reacting at room temperature, washing to neutrality after the reaction is completed, and drying to obtain modified wood fiber; S3, modification of silicon dioxide: adding silicon dioxide to the mixed solution, and then treating it under heating and stirring conditions. After the treatment is completed, centrifuging, washing and drying are performed to obtain modified silicon dioxide; S4. Compounding of tea polyphenols: adding the modified attapulgite obtained in step S1, the modified wood fiber obtained in step S2 and the modified silicon dioxide obtained in step S3 into water, stirring and then adding tea polyphenols, stirring under heating conditions, centrifuging and drying after the treatment, to obtain a modified composite filler.
4. The iodine-blocking packaging material according to claim 3, characterized in that: In step S1, the mass ratio of attapulgite to sodium hydroxide is 1:0.4-0.8, the high temperature treatment temperature is 790-805°C, and the treatment time is 0.5-4h.
5. The iodine-blocking packaging material according to claim 3, characterized in that: In step S1, the concentration of the hydrochloric acid solution is 0.5-2.5 mol / L; the mass ratio of attapulgite to the hydrochloric acid solution is 1 g: 8-12 mL; the shaking treatment rate is 150-200 rpm, and the shaking treatment time is 0.5-2 h; and the sieving mesh number is 100-200 mesh.
6. The iodine-blocking packaging material according to claim 3, characterized in that: In step S2, the mass ratio of wood fiber, sodium chloroacetate, water and sodium hydroxide is 1:1.2~2:20~30:1~1.5; the heating reaction temperature is 55~70°C, the heating reaction time is 2~8h; the reaction time at room temperature is 12~36h.
7. The iodine-blocking packaging material according to claim 3, characterized in that: In step S3, the mixed solution is obtained by mixing concentrated sulfuric acid and hydrogen peroxide, the concentration of concentrated sulfuric acid is 11-18 mol / L, the concentration of hydrogen peroxide is 8-12 mol / L, and the volume ratio of concentrated sulfuric acid to hydrogen peroxide is 1:2-4; the amount ratio of silicon dioxide to the mixed solution is 1 g:5-8 mL; the heating and stirring treatment temperature is 35-50 ° C, the treatment time is 0.5-4 h, and the stirring rate of the heating and stirring is 80-150 rpm.
8. The iodine-blocking packaging material according to claim 3, characterized in that: In step S4, the mass ratio of modified attapulgite, modified wood fiber, modified silica, tea polyphenols and water is 1:2~3:0.5~1:0.1~0.3:8~12; the heating temperature is 30~35°C, the stirring treatment time is 1~4h, and the stirring rate is 60~120rpm.
9. A method for preparing the iodine-blocking packaging material according to any one of claims 1 to 8, characterized in that: The steps include: (1) coating a vinyl resin heat-sealing adhesive on the surface of the aluminum foil layer and drying the adhesive to form a vinyl resin heat-sealing coating; (2) coating the surface of the vinyl resin heat seal coating with a PVA coating liquid, and drying the coating to form a modified PVA coating; (3) applying VC glue on the surface of the modified PVA coating and drying to form a VC glue coating; (4) applying polyurethane heat-sealing adhesive on the surface of the VC glue coating, and drying to form a polyurethane heat-sealing coating to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
10. The preparation method according to claim 9, characterized in that: The coating amount of vinyl resin heat sealant is 5~8g / m 2 ; The coating amount of PVA coating liquid is 4~6 g / m 2 ; The coating amount of VC glue is 4~6 g / m 2 ; The coating amount of polyurethane heat sealant is 5~8 g / m 2 .
Citation Information
Patent Citations
Iodine-resistant packaging material and production process thereof
CN117183483A
Preparation method of degradable plastic packing material
CN109082137A
Modified wood fiber reinforced vegetable protein adhesive as well as preparation method and application thereof
CN111171783A
Degradable food packaging bag and preparation method thereof
CN111320849A
Anti-static laminated wood floor and preparation method thereof
CN112852084A